Supporting Transition from Out of Home Care to Adulthood: Linked Data Is Central to The Compass Social Impact Bond - Sharon Williams; Mark Sipthorp; Nicholas Ivkovic; Alexander Inglis (International Journal of Population Data Science, 2020)
The COMPASS program supports young people to successfully transition from Out of Home Care to adulthood. COMPASS is a social impact bond partnership between Victorian government, not-for-profit organisations and investors. COMPASS uses linked data in every phase from design, to implementation, to outcome measurement.